2017
DOI: 10.1108/ijph-07-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Universal opt-out screening for hepatitis C virus (HCV) within correctional facilities is an effective intervention to improve public health

Abstract: PurposeWorldwide efforts to identify individuals infected with the hepatitis C virus (HCV) focus almost exclusively on community healthcare systems, thereby failing to reach high-risk populations and those with poor access to primary care. In the USA, community-based HCV testing policies and guidelines overlook correctional facilities, where HCV rates are believed to be as high as 40 percent. This is a missed opportunity: more than ten million Americans move through correctional facilities each year. Herein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
1
22
3
Order By: Relevance
“…Studies on the e cacy of a risk-based HCV strategy among marginalized populations are limited, and to date, case nding by surveys have been only done in high-income countries (18,19). Previous studies have shown bene ts for universal screening in correctional facilities, compared to the risk-based screening, which is in contrast to our ndings (18,24). A possible explanation could be that in Iran, no taboo exists around illicit drug use among the incarcerated population, which results in more reliable self-reported information (25).…”
Section: Discussioncontrasting
confidence: 87%
“…Studies on the e cacy of a risk-based HCV strategy among marginalized populations are limited, and to date, case nding by surveys have been only done in high-income countries (18,19). Previous studies have shown bene ts for universal screening in correctional facilities, compared to the risk-based screening, which is in contrast to our ndings (18,24). A possible explanation could be that in Iran, no taboo exists around illicit drug use among the incarcerated population, which results in more reliable self-reported information (25).…”
Section: Discussioncontrasting
confidence: 87%
“…In the UK, universal opt-out screening has been initiated as of 2015 in Scotland, 2016 in Wales, and April 2017 in England, and this will be expanded to all prisons in the coming years [ 40 ]. This is crucial, as a significantly higher uptake of testing has been shown to occur with opt-out procedures in prisons [ 41 43 ]. Furthermore, several trials have shown that improved screening with opt-out procedures and subsequent treatment with DAAs is cost-effective, despite the high costs of DAA treatments [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research found an inconsistent approach to HCV screening with many prisoners only being tested at their own request. Consideration should be given to introducing an opt-out screening program on committal to prison in Ireland [ 18 , 40 , 41 ]. This screening strategy has been shown to be cost effective and has the potential to reduce HCV transmission and HCV-related liver disease primarily in the community [ 40 , 42 ].…”
Section: Discussionmentioning
confidence: 99%